The Technology Transfer of a Data Framework in the Financial Cooperative Sector - Tirloni, Jhonata; Figueiredo, Josiel Maimone de; Araujo, Nelcileno V. de Souza (Anais da Escola Regional de Informática de Mato Grosso (ERI-MT); 2025: Anais da XIV Escola Regional de Informática de Mato Grosso, 2025)
Financial cooperatives constitute a dynamic ecosystem characterized by high-value, data-intensive innovation that generates substantial revenue. This paper examines the process of transferring a data science framework as a technological asset, using an illustrative case study centered on a member journey optimization project within a financial cooperative. The proposed framework builds on the Technology Package concept, integrating principles from intellectual property law, technology management, and business strategy. It demonstrates how aligning IP strategy with established technology transfer mechanisms can not only unlock new revenue streams but also foster intercooperation within the financial ecosystem.